Serum Zinc and Selenium Concentrations in Patients with Hypertrophy and Remodelling of the Left Ventricle Secondary to Arterial Hypertension - Paweł Gać; Karolina Czerwińska; Małgorzata Poręba; Adam Prokopowicz; Helena Martynowicz; Grzegorz Mazur; Rafał Poręba (MDPI AG, 2021)
The aim of the study was to assess the relationship between serum selenium and zinc concentrations (Se-S and Zn-S) and the left ventricle geometry in patients suffering from arterial hypertension. A total of 78 people with arterial hypertension (mean age: 53.72 ± 12.74 years) participated in the study. Se-S and Zn-S were determined in all patients. The type of left ventricular remodelling and hypertrophy was determined by the left ventricular mass index (LVMI) and relative wall thickness (RWT) measured by echocardiography. Se-S and Zn-S in the whole group were 89.84 ± 18.75 µg/L and 0.86 ± 0.13 mg/L. Normal left ventricular geometry was found in 28.2% of patients; left ventricular hypertrophy (LVH) in 71.8%, including concentric remodelling in 28.2%, concentric hypertrophy in 29.5%, and eccentric hypertrophy in 14.1%. LVH was statistically significantly more frequent in patients with Se-S < median compared to patients with Se-S ≥ median (87.2% vs. 56.4%, p < 0.05), as well as in patients with Zn-S < median compared to patients with Zn-S ≥ median (83.8% vs. 60.9%, p < 0.05). In hypertensive patients, older age, higher LDL cholesterol, higher fasting glucose, lower Se-S, and lower Zn-S were independently associated with LVH. In conclusion, in hypertensive patients, left ventricular hypertrophy may be associated with low levels of selenium and zinc in the serum.